Everything you need to know about caregiving for Parkinson's disease - Marie, Lianna, 1974- (Purdue University Press, 2020)
"Caregiving for those who suffer from Parkinson's disease comes with many challenges, from how to deal with guilt and loneliness to avoiding burnout and figuring out what to expect from an unpredictable disease. When giving care, too often caregivers neglect their own well-being. Everything You Need to Know About Caregiving for Parkinson's Disease is not just about caring for your loved one, but also about taking care of yourself. Lianna Marie served as her mother's caregiver for more than twenty years after she was diagnosed with Parkinson's disease. Drawing on firsthand experience, her training as a nurse, and the many stories of others she has helped and counseled over the years, Marie shares her wisdom and advice-practical and emotional. Written accessibly and without jargon, Everything You Need to Know provides an essential resource full of useful information for all caregivers of those with Parkinson's disease"--